Experimental device for chemical corrosion resistance of waste glass sand geopolymer concrete
By designing a chemical corrosion resistance experimental device for waste glass sand-ground polymer concrete combining soaking pools and control panels, the problems of cumbersome experimental steps and safety hazards in the prior art are solved, and the automated immersion and detection process is realized, and the testing efficiency and accuracy are improved.
Patent Information
- Application Number
- CN202421007483.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2034-05-10
AI Technical Summary
The prior art tests the chemical resistance of polymer concrete of waste glass sand, and the steps are complicated. When a person moves the soaked concrete, it is easy to affect the subsequent testing experiments, and the residual chemical liquid poses a threat to personnel's safety.
A chemical corrosion resistance experimental device for waste glass sand-ground polymer concrete is designed, combining the soaking pool and control panel to achieve an integrated setting of soaking and detection. The device automatically completes the immersion and removal process through an electro-hydraulic cylinder and lifting frame system, and is equipped with a force detection sensor to achieve automated detection.
The experimental steps are simplified, errors and safety risks of manual operation are reduced, the efficiency and accuracy of the test are improved, and the impact of different concentrations of chemical solutions on concrete can be effectively detected.
Smart Images

Figure CN222762046U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of concrete experimental devices, in particular to a waste glass sand polymer concrete anti-chemical corrosion experimental device. Background Art
[0002] Geopolymer concrete is a new green and low-carbon building material formed by mixing silicon-alumina raw materials (metakaolin, fly ash, slag, etc.), coarse and fine aggregates and alkali activators (NaOH solution, Na2SiO3 solution, etc.) in appropriate proportions through geopolymerization. Waste glass is an important component of urban solid waste and domestic garbage. In recent years, the use of waste glass to replace natural sand and gravel to prepare concrete has received widespread attention. However, the feasibility study of preparing geopolymer concrete with waste glass sand is still in the exploratory stage, especially the influence of different waste glass sand replacement rates on the mechanical and durability properties of geopolymer concrete. In order to obtain the chemical resistance of waste glass sand geopolymer concrete, different concentrations of sulfuric acid and chloride salts are usually set to soak it, and then pressure is applied to test the mechanical properties of waste glass sand geopolymer concrete to obtain the effects of sulfuric acid and chloride salts on it. However, this step is cumbersome, and the subsequent testing of concrete is easily affected when personnel move the soaked concrete, and the chemical liquid remaining in the concrete is easy to affect personnel safety. Utility Model Content
[0003] The technical problem to be solved by the utility model is to overcome the existing defects and provide a waste glass sand polymer concrete anti-chemical corrosion experimental device. The immersion and detection are integrated and there is no need for personnel to move the concrete after immersion. When the concrete is taken out of the chemical liquid, its mechanical properties can be tested in time to test the influence of sulfuric acid and chloride salt on it. In addition, the experimental device is convenient for setting up multiple groups of experimental control groups, which is convenient for comparative tests of chemical solutions of various concentrations, and can effectively solve the problems in the background technology.
[0004] To achieve the above-mentioned purpose, the utility model provides the following technical solutions: an experimental device for the chemical corrosion resistance of polymer concrete of waste glass sand, comprising a immersion tank and a control panel installed on the side of the immersion tank, wherein a plurality of immersion chambers are arranged in an array, a placement box is arranged in each of the immersion chambers, and the top of the placement box is open, a plurality of liquid inlets are opened on the lower side of the placement box, a positioning frame is installed on the upper side of the immersion tank, a movable plate is slidably provided on the side of the positioning frame, a lifting assembly for lifting the placement box is provided on the side of the movable plate, and an extrusion assembly is provided at the position corresponding to the placement box below the movable plate.
[0005] As an optimal technical solution of the utility model, extension plates are fixed on both sides of the placement box, a lifting frame is installed at the telescopic end of the lifting assembly, and the lifting frame is an inverted U-shaped structure, and a clamping frame is installed at the end of the lifting frame, and the clamping frame is clamped and adapted with the extension plate.
[0006] As a preferred technical solution of the utility model, the lifting assembly includes an electric hydraulic cylinder installed on the side of the movable plate, the telescopic end of the electric hydraulic cylinder is fixedly connected to the middle part of the side of the lifting frame, a guide rod is fixed to the side of the lifting frame, and the guide rod is slidably connected to the movable plate. The electric hydraulic cylinder, the control switch corresponding to the electric hydraulic cylinder in the control panel, and the external power supply are connected in series to form a working circuit of the electric hydraulic cylinder.
[0007] As a preferred technical solution of the utility model, a mounting plate is fixed to the telescopic end of the electric hydraulic cylinder, a force detection sensor is installed between the mounting plate and the lifting frame, and the force detection sensor, a control switch corresponding to the force detection sensor in the control panel, and an external power supply are connected in series to form a working circuit of the force detection sensor.
[0008] As a preferred technical solution of the utility model, the extrusion assembly includes a fixed rod installed on the side of the movable plate, and an extrusion plate is installed at the bottom end of the fixed rod, and the extrusion plate is located below the lifting frame.
[0009] As a preferred technical solution of the utility model, an adjusting screw is installed on the side of the positioning frame, a driving motor is installed on the side of the positioning frame, the output shaft of the driving motor is fixedly connected to the adjusting screw, a threaded barrel is installed on the side of the movable plate, the threaded barrel is connected to the adjusting screw by threads, and the driving motor, the control switch corresponding to the driving motor in the control panel, and the external power supply are connected in series to form a working circuit of the driving motor.
[0010] As a preferred technical solution of the utility model, a positioning frame is fixed at a position near the soaking chamber on the top of the soaking pool, and a shielding plate is arranged in the positioning frame, and a handle is fixed on the side of the shielding plate.
[0011] Compared with the prior art, the beneficial effects of the utility model are:
[0012] 1. The waste glass sand polymer concrete anti-chemical corrosion experimental device of the utility model example places the waste glass sand polymer concrete that needs to be soaked in chemical solution in a placement box, adds sulfuric acid solution or sodium chloride solution of different concentrations into several soaking chambers of the soaking pool, and soaks the waste glass sand polymer concrete with the set chemical solution. The soaking time can be flexibly set according to the test requirements. Control experiments are carried out by setting multiple groups of solutions, which is convenient for testing the chemical resistance of the waste glass sand polymer concrete.
[0013] 2. In the waste glass sand polymer concrete anti-chemical corrosion experimental device exemplified in the utility model, after immersion is completed, the control panel is used to control the driving motor to drive the adjusting screw to rotate, and the adjusting screw drives the movable plate to move along the positioning frame to adjust the position of the lifting frame. Then, the control panel is used to control the electric hydraulic cylinder to drive the lifting frame to move, and the position of the lifting frame is adjusted to connect the card frame with the extension plate. The electric hydraulic cylinder is used to drive the lifting frame to move up, so as to facilitate the removal of the placement box from the immersion chamber. The mobile lifting frame can be used to take and place the placement boxes at different positions, which is convenient for the use of the experimental device.
[0014] 3. In the waste glass sand polymer concrete anti-chemical corrosion experimental device of the utility model example, after the placement box is taken out from the immersion chamber, the immersion chamber is sealed by a shielding plate, and the electric hydraulic cylinder is continuously controlled to make the lifting frame drive the placement box to move upward, and the moving plate makes the extrusion plate contact with the waste glass sand polymer concrete through the fixed rod, and the waste glass sand polymer concrete is extruded by the extrusion plate. During the extrusion process, the force detection sensor detects the pressure, and feeds back the detection result to the control panel for recording and display, so that personnel can observe the test data and judge the influence of the chemical liquid on the waste glass sand polymer concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a structural schematic diagram of the utility model;
[0016] Figure 2 for Figure 1 Schematic diagram of the structure of the detection component;
[0017] Figure 3 for Figure 2 Schematic diagram of the enlarged structure at point A in the middle.
[0018] In the figure: 1 immersion tank, 2 positioning frame, 3 shielding plate, 4 handle, 5 positioning frame, 6 moving plate, 7 electric hydraulic cylinder, 8 mounting plate, 9 lifting frame, 10 clamping frame, 11 force detection sensor, 12 guide rod, 13 adjusting screw, 14 driving motor, 15 threaded cylinder, 16 placement box, 17 extension plate, 18 fixing rod, 19 extrusion plate, 20 control panel. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the utility model to clearly and completely describe the technical solutions in the embodiments of the utility model. Obviously, the described embodiments are only part of the embodiments of the utility model, not all of the embodiments. Based on the embodiments in the utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.
[0020] See also Figure 1-3 The utility model provides a technical solution: an experimental device for chemical corrosion resistance of waste glass sand polymer concrete, comprising a soaking pool 1 and a control panel 20 installed on the side of the soaking pool 1, the control panel 20 is a PLC controller with a display screen and a switch group, the control panel 20 is used to control the operation of the electronic components in the experimental device, and the control panel 20 is used to receive feedback information from some electronic components, a plurality of soaking chambers are arranged in an array, a plurality of soaking chambers are provided with placement boxes 16, and the top of the placement box 16 is open, the opening is convenient for the waste glass sand polymer concrete to be placed in the placement box 16, and is convenient for subsequent mechanical performance testing, a plurality of liquid inlets are provided at the lower part of the side of the placement box 16, which is convenient for the chemical liquid in the soaking chamber to enter the placement box 16 to soak the waste glass sand polymer concrete, a positioning frame 5 is installed on the upper side of the soaking pool 1, a moving plate 6 is slidingly provided on the side of the positioning frame 5, a lifting component for lifting the placement box 16 is provided on the side of the moving plate 6, and an extrusion component is provided at the position corresponding to the placement box 16 below the moving plate 6.
[0021] The waste glass sand polymer concrete that needs to be soaked in the chemical solution is placed in the placement box 16, and sulfuric acid solution or sodium chloride solution of different concentrations is added to the several soaking chambers of the soaking pool 1. The waste glass sand polymer concrete is soaked with the set chemical solution. The soaking time can be flexibly set according to the test requirements. Control experiments are carried out by setting multiple groups of solutions, which is convenient for testing the chemical resistance of the waste glass sand polymer concrete.
[0022] Extension plates 17 are fixed on both sides of the placement box 16, and a lifting frame 9 is installed at the telescopic end of the lifting assembly, and the lifting frame 9 is an inverted U-shaped structure. A clamping frame 10 is installed at the end of the lifting frame 9, and the clamping frame 10 is clamped and adapted with the extension plate 17. The clamping frame 10 is clamped with the extension plate 17 by adjusting the position of the lifting frame 9, so that the placement box 16 can be taken out of the immersion chamber by the lifting assembly, and then it can be squeezed by the extrusion assembly. Test.
[0023] The lifting assembly includes an electric hydraulic cylinder 7 installed on the side of the movable plate 6. The telescopic end of the electric hydraulic cylinder 7 is fixedly connected to the middle part of the side of the lifting frame 9. A guide rod 12 is fixed to the side of the lifting frame 9. The guide rod 12 is slidably connected to the movable plate 6. The electric hydraulic cylinder 7, the control switch corresponding to the electric hydraulic cylinder 7 in the control panel 20, and the external power supply are connected in series to form a working circuit of the electric hydraulic cylinder 7. The electric hydraulic cylinder 7 is controlled to work through the control panel 20, and the lifting frame 9 is driven by the electric hydraulic cylinder 7 to move. The position of the lifting frame 9 is adjusted to clamp the connecting frame 10 with the extension plate 17. The lifting frame 9 is driven upward by the electric hydraulic cylinder 7 to facilitate the removal of the placement box 16 from the immersion chamber. The mobile lifting frame 9 can be used to take and place the placement boxes 16 at different positions, which is convenient for the use of this experimental device.
[0024] A mounting plate 8 is fixed to the telescopic end of the electric hydraulic cylinder 7, and a force detection sensor 11 is installed between the mounting plate 8 and the lifting frame 9. The force detection sensor 11, the control switch corresponding to the force detection sensor 11 in the control panel 20, and the external power supply are connected in series to form a working circuit of the force detection sensor 11. After the placement box 16 is taken out of the immersion chamber, the extrusion assembly extrude the waste glass sand polymer concrete. During the extrusion process, the force detection sensor 11 detects the pressure and feeds back the detection result to the control panel 20 for recording and display, so that personnel can observe the test data and judge the influence of the chemical liquid on the waste glass sand polymer concrete.
[0025] The extrusion assembly includes a fixed rod 18 installed on the side of the movable plate 6, and an extrusion plate 19 is installed at the bottom end of the fixed rod 18. The extrusion plate 19 is located below the lifting frame 9. The electric hydraulic cylinder 7 is controlled to work so that the lifting frame 9 drives the placement box 16 to move upward. The movable plate 6 makes the extrusion plate 19 contact with the waste glass sand polymer concrete through the fixed rod 18, and the waste glass sand polymer concrete is extruded through the extrusion plate 19.
[0026] An adjusting screw 13 is installed on the side of the positioning frame 5, and a driving motor 14 is installed on the side of the positioning frame 5. The output shaft of the driving motor 14 is fixedly connected to the adjusting screw 13. A threaded barrel 15 is installed on the side of the movable plate 6, and the threaded barrel 15 is connected to the adjusting screw 13 by threads. The driving motor 14, the control switch corresponding to the driving motor 14 in the control panel 20, and the external power supply are connected in series to form a working circuit of the driving motor 14. After the soaking is completed, the driving motor 14 is controlled by the control panel 20 to drive the adjusting screw 13 to rotate, and the adjusting screw 13 drives the movable plate 6 to move along the positioning frame 5 to adjust the position of the lifting frame 9. The lifting frame 9 can be used to take and place the placement boxes 16 at different positions, which is convenient for the use of this experimental device.
[0027] A positioning frame 2 is fixed at the top of the immersion pool 1 near the immersion chamber, and a baffle plate 3 is arranged in the positioning frame 2. A handle 4 is fixed on the side of the baffle plate 3. When the placement box 16 is taken out of the immersion chamber, the immersion chamber is sealed by the baffle plate 3, which is convenient for the mechanical properties experiment of the waste glass sand polymer concrete.
[0028] The electric hydraulic cylinder 7, force detection sensor 11, drive motor 14 and control panel 20 used in the present invention are all commonly used electronic components in the prior art, and controlling the working mode of the electric hydraulic cylinder 7, force detection sensor 11, drive motor 14 and other electronic components through the control panel 20 is a common technical means used by technicians, and their working methods and circuit structures are well-known technologies and will not be elaborated here.
[0029] When using:
[0030] The waste glass sand polymer concrete that needs to be soaked in the chemical solution is placed in the placement box 16, and sulfuric acid solutions or sodium chloride solutions of different concentrations are added to the soaking chambers of the soaking pool 1. The waste glass sand polymer concrete is soaked with the set chemical solution. The soaking time can be flexibly set according to the test requirements. The control experiment is carried out by setting multiple groups of solutions, which is convenient for testing the chemical resistance of the waste glass sand polymer concrete.
[0031] After the soaking is completed, the control panel 20 controls the driving motor 14 to work and drive the adjusting screw 13 to rotate, and the adjusting screw 13 drives the moving plate 6 to move along the positioning frame 5 to adjust the position of the lifting frame 9. Then, the control panel 20 controls the electric hydraulic cylinder 7 to work, and the electric hydraulic cylinder 7 drives the lifting frame 9 to move. By adjusting the position of the lifting frame 9, the clamping frame 10 is clamped with the extension plate 17. The electric hydraulic cylinder 7 drives the lifting frame 9 to move up to facilitate the removal of the placement box 16 from the soaking chamber. By moving the lifting frame 9, it can be used to take and place the placement boxes 16 at different positions, which is convenient for the use of this experimental device.
[0032] After the placement box 16 is taken out from the immersion chamber, the immersion chamber is sealed by the shielding plate 3, and the electric hydraulic cylinder 7 is continuously controlled to make the lifting frame 9 drive the placement box 16 to move upward, and the movable plate 6 makes the extrusion plate 19 contact with the waste glass sand polymer concrete through the fixed rod 18, and the waste glass sand polymer concrete is extruded by the extrusion plate 19. During the extrusion process, the force detection sensor 11 detects the pressure and feeds back the detection result to the control panel 20 for recording and display, so as to facilitate personnel to observe the test data and judge the influence of the chemical liquid on the waste glass sand polymer concrete.
[0033] The undisclosed parts in the present utility model are all prior art, and their specific structures, materials and working principles are not described in detail. Although the embodiments of the present utility model have been shown and described, it is understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present utility model, and the scope of the present utility model is defined by the attached claims and their equivalents.
Claims
1. A waste glass sand polymer concrete anti-chemical corrosion experimental device, comprising a soaking tank (1) and a control panel (20) installed on the side of the soaking tank (1), characterized in that: The soaking pool (1) is provided with a plurality of soaking chambers, and the plurality of soaking chambers are arranged in an array shape. A placement box (16) is provided in each of the soaking chambers, and the top of the placement box (16) is open. A plurality of liquid inlets are provided at the lower side of the side of the placement box (16). A positioning frame (5) is installed on the upper side of the soaking pool (1). A movable plate (6) is slidably provided on the side of the positioning frame (5). A lifting component for lifting the placement box (16) is provided on the side of the movable plate (6). A pressing component is provided at a position corresponding to the placement box (16) below the movable plate (6).
2. The waste glass sand polymer concrete anti-chemical corrosion experimental device according to claim 1 is characterized by: Extension plates (17) are fixed on both sides of the placement box (16); a lifting frame (9) is installed at the telescopic end of the lifting assembly, and the lifting frame (9) is an inverted U-shaped structure; a clamping frame (10) is installed at the end of the lifting frame (9), and the clamping frame (10) is clamped and adapted to the extension plate (17).
3. The waste glass sand polymer concrete anti-chemical corrosion experimental device according to claim 2 is characterized by: The lifting assembly comprises an electric hydraulic cylinder (7) mounted on the side of the movable plate (6); the telescopic end of the electric hydraulic cylinder (7) is fixedly connected to the middle of the side of the lifting frame (9); a guide rod (12) is fixed to the side of the lifting frame (9); the guide rod (12) is slidably connected to the movable plate (6); the electric hydraulic cylinder (7), a control switch corresponding to the electric hydraulic cylinder (7) in the control panel (20), and an external power supply are connected in series to form a working circuit of the electric hydraulic cylinder (7).
4. The waste glass sand polymer concrete anti-chemical corrosion experimental device according to claim 3 is characterized by: A mounting plate (8) is fixed to the telescopic end of the electric hydraulic cylinder (7), and a force detection sensor (11) is installed between the mounting plate (8) and the lifting frame (9). The force detection sensor (11), a control switch corresponding to the force detection sensor (11) in the control panel (20), and an external power supply are connected in series to form a working circuit of the force detection sensor (11).
5. The waste glass sand polymer concrete anti-chemical corrosion experimental device according to claim 1 is characterized by: The extrusion assembly comprises a fixed rod (18) mounted on the side of the movable plate (6), a pressing plate (19) being mounted on the bottom end of the fixed rod (18), and the pressing plate (19) is located below the lifting frame (9).
6. The waste glass sand polymer concrete anti-chemical corrosion experimental device according to claim 1 is characterized by: An adjusting screw (13) is mounted on the side of the positioning frame (5), a driving motor (14) is mounted on the side of the positioning frame (5), an output shaft of the driving motor (14) is fixedly connected to the adjusting screw (13), a threaded barrel (15) is mounted on the side of the movable plate (6), the threaded barrel (15) is connected to the adjusting screw (13) by threads, and the driving motor (14), a control switch corresponding to the driving motor (14) in the control panel (20), and an external power supply are connected in series to form a working circuit of the driving motor (14).
7. The waste glass sand polymer concrete anti-chemical corrosion experimental device according to claim 1 is characterized by: A positioning frame (2) is fixed at a position near the soaking chamber on the top of the soaking pool (1), and a shielding plate (3) is arranged inside the positioning frame (2). A handle (4) is fixed on the side of the shielding plate (3).